Racial and Ethnic Differences Between Obstetrician-Gynecologists and Other Adult Medical Specialists - Rayburn, William F; Xierali, Imam M; Castillo-Page, Laura; Nivet, Marc A (Obstetrics and gynecology (New York. 1953), 2016)
To compare racial and ethnic differences between obstetrician-gynecologists (ob-gyns) and other large groups of adult medical specialists who provide the predominant care of women. Whether physician diversity influences their practice locations in underserved areas was also sought. This cross-sectional study reports an analysis of U.S. national data about racial and ethnic characteristics, gender, and specialty (obstetrics and gynecology, general internal medicine, family medicine, emergency medicine) of 190,379 physicians who came from three resources (Association of American Medical Colleges Student Records System, Association of American Medical Colleges Minority Physicians Database, American Medical Association Physician Masterfile). Underserved locations were identified as being rural, having 20% or more of the population living in poverty or being federally designated as areas of professional shortages or underserved populations. Bivariate measures of associations were performed to study the association between physician race and ethnicity and their practice location. Female physicians in all specialties were more likely than males to be nonwhite, and ob-gyns were most likely to be female (61.9%). Compared with other studied specialists, ob-gyns had the highest proportion of underrepresented minorities (combined, 18.4%), especially black (11.1%) and Hispanic (6.7%) physicians. Underrepresented minority ob-gyns were more likely than white or Asians to practice in federally funded underserved areas or where poverty levels were high. Native Americans, Alaska Natives, and Pacific Islanders were the ob-gyn group with the highest proportion practicing in rural areas. Compared with other adult medical specialists, ob-gyns have a relatively high proportion of black and Hispanic physicians. A higher proportion of underrepresented minority ob-gyns practiced at medically underserved areas.